Nonlinear effects in the regularity problems for infinite dimensional evolutions of unbounded spin systems - Antoniouk, A.Val.; Antoniouk, A.Vict. (Condensed Matter Physics, 2006)
We study the regularity problems for unbounded spin systems of anharmonic oscillators, that approximate multi-dimensional Euclidean field theories. The main attention is paid to the effect of anharmonism on the C∞-regularity properties of evolutional semigroup. Our approach is based on a new class of nonlinear estimates on variations, that permit to obtain regular properties for essentially nonlinear equations.